Implementasi nilai karakter kejujuran melalui permainan tradisional congklak pada hari tumpah budaya (HTB) di TK Kusuma Bangsa Keben Turi Lamongan - Siti Fatimah; Akbar, Sa’dun; Suryanto, Hadi; Ghofur, Abd.; Nurdiana, Ratna (PPPM STKIP PGRI Lamongan, 2024)
Honesty is a very important moral value in human life. Without honesty, relationships between individuals, families and communities can be damaged. Therefore, it is important to teach the value of honesty to children from an early age so that they grow into honest and responsible individuals through traditional games. This study aims to describe the implementation of character education through the traditional congklak game on the Hari Tumpah Budaya (HTB) at TK Kusuma Bangsa Keben Turi Lamongan. The method used in this research is a qualitative research method, with a descriptive research type. As for the determination of research subjects using purposive techniques, with data collection techniques using observation, interviews and documentation. While the data analysis uses descriptive analysis with the Miles and Hubberman models, namely data condensation, presentation and conclusions. To test the validity of the data using source and technique triangulation. The results of this study are that there is an application of honest character, namely honesty in relationships between children and honesty in self-acceptance. In addition, the research also identified the impacts, problems and solutions that arise in the implementation of honest character values through the traditional congklak game on the Hari Tumpah Budaya (HTB) at TK Kusuma Bangsa Keben Turi Lamongan. Keywords: implementation, honesty, congklak